Market efficiency and calendar anomalies in commodity futures markets: a review - Damini Chhabra; Mohit Gupta (Agricultural Economics Research Review, 2023)
This study reviews the literature on market efficiency and calendar anomalies in agricultural commodity futures markets in India and abroad. The study finds that most studies used ordinary least squares regression analysis to test for the weak form of market efficiency and only a few markets are found to be weakly efficient. Many studies that depict market inefficiency report the presence of calendar anomalies in metals and agricultural commodity futures. The most frequently observed calendar anomalies are the day-of-the-week effect and the month-of-the-year effect. Knowing about these market inefficiencies may help commodity market players formulate their purchase, sale, and trading strategies.